Debt-Related Financial Hardship and Health. (December 2021) - Sweet, Elizabeth
Recent research shows personal financial debt is an important socioeconomic determinant of health, but the mechanisms through which it operates are not well understood. This article uses data from a mixed-methods study to explore how changes in spending and behavior that result from debt have salient health consequences in a cross-sectional sample of Boston area adults ( n = 286). Findings show that a large majority of respondents had skipped medical care, housing payments, or consumer purchases at least once because of their debt. Controlling for multiple sociodemographic characteristics, each of these measures of debt-related behavior change was associated with worse self-rated health, and higher depressive symptoms, anxiety, and perceived stress. In models including all three measures, skipped medical care was associated with worse health across all outcomes, while skipped consumer purchases were associated with higher perceived stress and depression. These findings suggest that altered spending and care-seeking behaviors are potential pathways through which financial debt can negatively affect health and suggest areas in need of additional research.